The Purpose of a Students Affairs Program Within Jesuit Higher Education - Stringer, Jeremy; Swezey, Erin (Catholic Education: A Journal of Inquiry and Practice, 2006)
This article addresses the congruence of a student affairs professional preparation program within Jesuit higher education. It connects the mission of Jesuit education and Jesuit religious and educational principles to the philosophy of student affairs work in colleges and universities. A program in student development administration at Seattle University is presented as an example of how a student affairs preparation program honors Jesuit principles.